Unusual Presentation of Metastasis to the Ascending Colon from Squamous Cell Carcinoma of the Cervix - Ganesarajah, Selvaluxmy; Christopher, Vasanth; Madhavan, Ram; P.R., Vengada Krishnan (Asian Pacific Journal of Cancer Care, 2023)
Background: Metastasis to the ascending colon from primary carcinoma of the cervix is an uncommon occurrence. Squamous cell carcinoma (SCC) of the cervix can metastasize to unusual sites, including the bones, stomach, duodenum, colon, and skin. SCC of the cervix is a rare malignancy of the gastrointestinal tract (GI). Metastasis of SCC of the cervix to the GI tract is infrequent and has only been reported in a few cases. This condition can manifest as intestinal obstruction, often requiring debulking surgery. The management is typically palliative, and the role of chemotherapy or radiation therapy remains unclear. Case Presentation: In this report, we present the case of a 47-year-old female with a history of squamous cell carcinoma of the cervix, initially treated in 2014. She experienced local recurrence in 2019 and underwent pelvic re-radiation. Subsequently, she presented with intestinal obstruction, and further evaluation revealed metastatic squamous cell carcinoma in the ascending colon.